The Effect of Some Environmental Factors on the Survival Characteristics of Flexibacter chinensis (Journal of Sciences, Islamic Republic of Iran)
To survive in natural waters, bacteria must respond to variety of environmental factors. Flexibacter survival in the aquatic environment is influenced by number of parameters, such as temperature, heavy metal concentration and oxidation. Here we investigate the influence of these factors on the survival of Flexibacter chinensis in starvation medium. Our data shows that different concentrations of hydrogen peroxide decrease the survival time of bacteria while they have no influence on total count. Also, the investigation about the effect of heat shock on this bacterium demonstrates that the increasing of temperature leads to viability decrease. At least, the examination of the effect of heavy metal ions on the survival of F. chinensis shows that Zinc had less inhibitor activity on the cell viability in comparison to Cadmium and Copper.